Tiny magnetic resonance imaging black spot - Presenting an interesting case of internuclear ophthalmoplegia with radioanatomical correlation - Rai, Santosh; Dudekula, Anees; Kedambadi, Rakshith; Pai, Shivananda (Indian Journal of Case Reports, 2018)
Horizontal gaze palsy involves three different entities of similar imaging findings with subtle differences and a prominent difference in the clinical findings. A thorough knowledge of the anatomy of the pathway of horizontal gaze pathways is essential before coming to the correct diagnosis. Here, we report the case of a 42-year-old male patient presented with a history of impaired vision for 1 day. Through this case report, we will revisit these three entities with a brief discussion on the pathways involved in horizontal gaze palsies.